Valorization of agro-forest wastes (oak acorns, vineyard pruning, and olive pruning) through the cultivation of shiitake (Lentinula edodes) mushrooms - Youssef Najib Sassine; Stephanie Nabhan; Elina Rachkidy; Zeina El Sebaaly (Heliyon, 2024)
Experimental research has been focusing on developing new substrates for growing shiitake mushrooms as alternatives to the standard oak sawdust substrate. The selection of appropriate lignocellulosic materials is based on their availability in the production area and their compatibility with the requirements of the mushroom species being cultivated. In comparison to oak sawdust substrate (OS) as the control, this study evaluated the potential of oak acorns (OA), olive pruning (OLPR), and vineyard pruning (VIP), and various combinations: OA-OLPR:1-1, OA-VIP:1-1, OS-OLPR:1-1, and OS-VIP:1-1, prepared on a dry weight basis. In comparison to OS, complete mycelial development was hastened in OA, OA-VIP: 1-1, and OS-VIP:1-1 by 9.5, 7.9, and 4.2 days and delayed in OLPR and OS-OLPR:1-1 by 11.3 and 7.0 days, respectively. Also, harvest was earlier in OA, OA-VIP:1-1, and OS-VIP:1-1 by 9.3, 6.7, and 3.3 days, respectively, while it was significantly delayed in OLPR, VIP, and OS-OLPR:1-1 by 12.3, 3.7, and 8.0 days, respectively. While the total biological yield was significantly reduced in OLPR, OS-OLPR:1-1, VIP, and OS-VIP:1-1, it was comparable to OS in OA, OA-OLPR:1-1, and OA-VIP:1-1 (597.0, 552.0, 532.2, and 556.2 g/kg, respectively). Production was consistently high over two consecutive flushes in OS, OA, and OA-VIP: 1-1. Total biological yields were higher in OA-OLPR: 1-1 than OS-OLPR:1-1 and in OA-VIP:1-1 than OS-VIP:1-1. OA increased mushroom number and firmness, VIP and OLPR increased mushroom weight, and OA-VIP:1-1 increased pileus thickness. Mushrooms’ protein and fiber contents were higher than OS in all substrates and the highest in OA-OLPR:1-1 (8.7 %) and OLPR (2.8 %), respectively. Conclusively, the substrates OA, OA-VIP: 1-1, and OA-OLPR:1–1 may alternate oak sawdust; however, the first two substrates have an advantage over the third due to earlier harvests. Also, it is more favorable to use VIP and OLPR in combination with OA than to use them alone.